2021
DOI: 10.1093/cvr/cvab263
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial tissue factor contributes to trimethylamine N-oxide-enhanced arterial thrombosis

Abstract: Aims Gut microbiota and their generated metabolites impact the host vascular phenotype. The metaorganismal metabolite trimethylamine N-oxide (TMAO) is both associated with adverse clinical thromboembolic events, and enhances platelet responsiveness in subjects. The impact of TMAO on vascular tissue factor (TF) in vivo is unknown. Here, we explore whether TMAO-enhanced thrombosis potential extends beyond TMAO effects on platelets, and is linked to TF. We also further explore the links between … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 101 publications
0
36
0
1
Order By: Relevance
“…Direct PAR1 inhibition via provision of vorapaxar reduced the expression of VCAM-1 and E-selectin ( Figure 5 A,B) in aortic specimens from ApoEko mice (relative mean fluorescence intensity of VCAM-1 in aortic plaques ± SD control vs. vorapaxar; n = 6: 1.0 ± 0.2 vs. 0.14 ± 0.08, p < 0.0001). Tissue factor contributes critically to in vivo atherothrombosis initiation and a procoagulant state [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. In our model, treatment with vorapaxar also affected the aortic expression of TF ( Figure 5 A).…”
Section: Resultsmentioning
confidence: 99%
“…Direct PAR1 inhibition via provision of vorapaxar reduced the expression of VCAM-1 and E-selectin ( Figure 5 A,B) in aortic specimens from ApoEko mice (relative mean fluorescence intensity of VCAM-1 in aortic plaques ± SD control vs. vorapaxar; n = 6: 1.0 ± 0.2 vs. 0.14 ± 0.08, p < 0.0001). Tissue factor contributes critically to in vivo atherothrombosis initiation and a procoagulant state [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. In our model, treatment with vorapaxar also affected the aortic expression of TF ( Figure 5 A).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, in two clinical studies using optical coherence tomography to assess coronary plaque characteristics, increased plasma trimethylamine-N-oxide levels were linked to increased incidence of plaque rupture supporting a critical role of TMAO in vascular inflammation ( 227 , 242 ). Beyond the pathomechanistic link between TMAO and atherosclerotic plaque development, TMAO has also been reported to promote atherothrombosis by increased platelet activation ( 243 ) and tissue factor expression in endothelial cells ( 244 ). In recent studies, microbial enzymes that process the generation of TMA have been targeted using small molecule inhibitors that can modulate TMA/TMAO levels and detrimental cardiovascular effects in experimental settings ( 245 ).…”
Section: Gut Microbiota-dependent Modulation Of Atherogenesis and Plaque Phenotypementioning
confidence: 99%
“…Recent investigations have demonstrated that TMAO enhances platelet reactivity by promoting ERK1/2 and Jun N-terminal kinase (JNK) phosphorylation ( 49 ). In vivo and in vitro experiments have revealed that TMAO increases thrombotic potential by strengthening aortic vascular tissue factor (TF) and vascular cell adhesion molecule (VCAM)1 expression ( 50 ).…”
Section: The Source Synthesis and Metabolism Of Tmaomentioning
confidence: 99%
“…Existing reports show that IMC can suppress choline diet-enhanced platelet aggregation and the in vivo rate of thrombus formation without increased bleeding time ( 16 ), and it can also alter host cholesterol and bile acid metabolism in preclinical animal models ( 82 ). In addition, a TF-inhibitory antibody or FMC can abrogate TMAO-dependent enhancements of in vivo TF expression and thrombogenicity ( 50 ). Reportedly, Meldonium lowers the production of TMA by inhibiting the L-carnitine metabolism intermediate γ-butyl betaine ( 83 ).…”
Section: Preventions and Treatments Targeting Tmaomentioning
confidence: 99%